Pengaruh Inovasi Dan Kualitas Produk Terhadap Keberhasilan Usaha Pada Home Industri Sepatu Di Balaraja Tangerang - Rousdy Safari Tamba; Siti Nurfadillah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to identify and analyze The Effect of Innovation and Product Quality on Business Success in the Home Shoes Industry in Balaraja Tangerang. The research method used is a quantitative method. Data collection techniques used in the form of questionnaires and literature. The population used in this study were 25 home business actors in the shoe industry in Balaraja, Tangerang. The sampling technique in this study is the technique Non Probability Sampling with the method Saturated Sampling, and the sample used in this study is the entire population. Based on the results of t test (partial test) from the calculation of the variable Innovation (X1) a significant effect on business success (Y) because tcount 3,288> ttable 2.074 and the significant value of 0.003> 0.05 and the coefficient of determination of 32%. T test results Product Quality variable (X2) significantly affects the success of the business (Y) because tcount 6,189> ttable 2.074 and 0.000 significant value of <0.05 and the coefficient of determination of 62.5%. Based on the research results obtained by the f test (simultaneous test) it can be concluded that Innovation (X1) and Product Quality (X2) together have a significant effect on Business Success (Y) because fcount 18.335> ftable 3.44 with a significant value of < 0.05 and the coefficient of determination is 62.5% while the remaining 37.5% is influenced by other variables not examined in this study